2021
DOI: 10.1186/s12866-020-02079-w
|View full text |Cite
|
Sign up to set email alerts
|

Revealing biophysical properties of KfrA-type proteins as a novel class of cytoskeletal, coiled-coil plasmid-encoded proteins

Abstract: Background DNA binding KfrA-type proteins of broad-host-range bacterial plasmids belonging to IncP-1 and IncU incompatibility groups are characterized by globular N-terminal head domains and long alpha-helical coiled-coil tails. They have been shown to act as transcriptional auto-regulators. Results This study was focused on two members of the growing family of KfrA-type proteins encoded by the broad-host-range plasmids, R751 of IncP-1β and RA3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In the RA3 plasmid of the IncU group, KfrC could interact directly not only with KfrA but also with KorB ( Figure 8 A), one of the components of the active partition system [ 18 ]. It was shown that KfrA RA3 had the ability to form filaments [ 29 ] and interacted with both components of the partition apparatus, KorB and IncC. Hence, the accessory role of a scaffold built of Kfr complexes in the segregation of plasmid molecules to the progeny cells in a species-dependent manner was envisaged [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the RA3 plasmid of the IncU group, KfrC could interact directly not only with KfrA but also with KorB ( Figure 8 A), one of the components of the active partition system [ 18 ]. It was shown that KfrA RA3 had the ability to form filaments [ 29 ] and interacted with both components of the partition apparatus, KorB and IncC. Hence, the accessory role of a scaffold built of Kfr complexes in the segregation of plasmid molecules to the progeny cells in a species-dependent manner was envisaged [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the stabilization module, upstream of the type Ia active partition system encoding KorB of the ParB family and IncC, the Walker-type ATPase of the ParA family, there are two structural genes for alpha-helical proteins KfrA and KfrC [ 22 , 28 ]. It has been shown recently that KfrA acts as a transcriptional autoregulator and is able to form long filamentous structures in the presence of plasmids carrying its cognate binding site [ 18 , 29 ]. Moreover, it forms a complex with KfrC and with both active partitioning proteins, KorB and IncC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation